Financial Statements–Form, Analysis, and Interpretation (Book). - Zeff, Stephen A.; Price, Harry R. (The Accounting Review, 1963)
Reviews the book "Financial Statements–Form, Analysis, and Interpretation," by Ralph Dale Kennedy and Stewart Y. McMullen.